k+6/26=1

Simple and best practice solution for k+6/26=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k+6/26=1 equation:



k+6/26=1
We move all terms to the left:
k+6/26-(1)=0
determiningTheFunctionDomain k-1+6/26=0
We multiply all the terms by the denominator
k*26+6-1*26=0
We add all the numbers together, and all the variables
k*26-20=0
Wy multiply elements
26k-20=0
We move all terms containing k to the left, all other terms to the right
26k=20
k=20/26
k=10/13

See similar equations:

| x2=58(x−4) | | w+68=-40 | | 80=10(3+x) | | x/2=5/8(x-4) | | 3(1+3n)+4=61 | | -23-(-38)=x/6 | | -3=-4+m/8 | | 6/x-10=2 | | 8x=-1/12-5/6 | | -8(4+r)=-144 | | g^2–12g+20=0 | | m-4/9=257/90 | | m-13=-10 | | 3(6k-1)=69 | | 5/4=x/2-1/6 | | 2.4z+6.3=-1.7z+47.1 | | -15=k/7 | | x-(-53/5)=41/2 | | 4x+6-10=3x-2 | | 0.2(100+x)=30+0.10 | | 0.6b+0.43=0.9b+0.7 | | 70=1/2x(6+1) | | 20+a=11 | | 0.6b=0.43=0.9b+0.7 | | -6=x/19 | | 5/8+16/8=x-5/8 | | (x+29)+110=180 | | 9a+4=5a-16 | | -6(n+6)=-72 | | 2+(x+8)÷3+1=0 | | 0.14-0.02(x+2)=0.04(2-x) | | 16m+3/4=1/8 |

Equations solver categories